Impact of CSR activities on customer trust and loyalty in the banking sector of Bangladesh - Md. Hazrat Ali; Md. Monirul Islam; Nusrat Afrin Nadi; Al Amin; Md. Mohibul Alam Dolon (Global Academy of Multidisciplinary Studies, 2025)
Purpose: The purpose of this study is to examine how Corporate Social Responsibility (CSR) practices in Bangladeshi banks influence customer trust and loyalty. It aims to understand whether CSR helps banks gain a competitive advantage, build stronger customer relationships, and improve long-term sustainability and profitability. Methods: This study uses a quantitative research approach. Data will be collected through a structured survey using stratified random sampling of 300 customers from at least five major banks in Bangladesh known for their CSR activities. The survey focuses on customer awareness, perception of CSR initiatives, trust, and loyalty, supported by secondary data such as CSR reports and academic literature. Data will be analyzed using descriptive statistics, correlation, and regression analysis, covering CSR dimensions such as community engagement, environmental sustainability, and financial inclusion in both urban and rural areas. Results: The study is expected to show that strong CSR practices improve customer perceptions of a bank’s ethics, reliability, and honesty, which boosts customer trust. Higher trust is likely to lead to greater customer loyalty, including retention and positive word-of-mouth. Banks that communicate CSR activities clearly are also expected to gain more satisfaction and brand advocacy. Findings will identify which CSR activities matter most and how they strengthen long-term customer relationships and competitive advantage. Conclusion: CSR is expected to significantly enhance customer trust and loyalty and reinforce sustainable competitive positioning for banks in Bangladesh. Limitation: This study is limited to selected banks and relies on self-reported survey responses, which may not fully capture customer behavior across the entire banking sector. Contribution: This study contributes to CSR, marketing, and banking strategy by providing empirical evidence on how CSR shapes trust and loyalty. It offers practical guidance for banks and policymakers and provides insights relevant to other developing countries.